GAYA BAHASA SARKASME DALAM KOLOM KOMENTAR DI AKUN TIKTOK @DEDYCOMBUZER KAJIAN SEMANTIK - Dwi Aprilia; Fajar Setiawan; Fatmawati (PT. Hasba Edukasi Mandiri, 2025)
This study explores the use of sarcastic language style in TikTok comments on @DeddyCorbuzier’s account as a response to legal injustice issues in Indonesia. Employing a qualitative approach and content analysis method, the researcher identified eleven sarcastic comments reflecting expressions of disappointment, criticism, and social protest against unequal legal treatment, particularly between minor and major offenses. Sarcasm here functions as a form of implicit communication, often expressed through irony, mockery, and dark humor. The findings suggest that sarcasm serves not only as emotional expression but also as a creative and strategic medium to voice social criticism and demand justice in the digital era. This research contributes to the study of semantics and language style within the context of digital communication.